080 La maladie anglaise: a case of Neurosyphilis in a HIV-negative patient. Issue 3 (9th February 2012) - Wright, B; Davies, M B D
Abstract : We report a very rare case of neurosyphilis in a HIV negative man. He presented with a sub-acute lymphocytic meningoencephalitis, later complicated by memory impairment, personality change and seizures. A 51-year-old, Caucasian, right-handed, warehouseman presented to his local hospital complaining of an unwitnessed collapse. Over the preceding 4 months he had had a dull, continuous, holocranial headache, with severe worsening prior to the collapse. He had increased frequency of episodic memory impairment and his weight had decreased by three stone over 3 months. Clinical examination revealed an apyrexial, unkempt man with multi-domain memory impairment. The rest of the general and neurological examination was normal. Initial investigations revealed normal or non-specific neuroradiological appearances, an abnormal EEG and a lymphocytic cerebrospinal fluid. Treatment for a presumed viral pathogen was clinically ineffective, with further memory decline, disinhibition, pathological laughter, and generalised seizures. Other investigations are notable for two asymptomatic pulmonary emboli, a false-positive anti-cardiolipin antibody, and a low-positive anti-thyroid peroxidise antibody. Repeated HIV serum serology was negative. Diagnosis was made from high positive serum and cerebrospinal fluid treponema antibody serology in the context of an evolving clinical, neuroradiological, and EEG picture. Subsequent Penicillin treatment was complicated by a self-limiting peticheal rash. He made a good clinical recovery, with improvement in his memory, behaviour, neuroradiology and EEG.